2021
DOI: 10.1021/acsbiomaterials.1c00467
|View full text |Cite
|
Sign up to set email alerts
|

Highly Absorbent Silk Fibroin Protein Xerogel

Abstract: Highly absorbent polymers have a wide range of applications in biomaterials, agriculture, physiological products of daily uses, and others. Silk fibroin, as a natural biomaterial with excellent biocompatibility and tunable mechanical properties, shows good prospects in the field of biomedicine applications. However, the dried fibroin hydrogel has very low absorbency. In this work, silk fibroin protein is used as the carrier, riboflavin as the photosensitizer, and accordingly, the hydrogel is prepared by free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The addition of this much nanocellulose in the polymeric matrix increased the brittleness of the xerogels, which is the main cause of xerogel fracture. Silk fibroin-based xerogels possess great water absorption capacity, and Cheng et al [ 23 ] reported that their xerogels were able to absorb up to 90 times its own mass of water within a minute in addition to its great hemostatic properties, making such material suitable for absorbing other body exudates. Several attempts have been made to produce aerogel-like xerogels under ambient conditions to minimize the shrinkage.…”
Section: Xerogel Functional Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of this much nanocellulose in the polymeric matrix increased the brittleness of the xerogels, which is the main cause of xerogel fracture. Silk fibroin-based xerogels possess great water absorption capacity, and Cheng et al [ 23 ] reported that their xerogels were able to absorb up to 90 times its own mass of water within a minute in addition to its great hemostatic properties, making such material suitable for absorbing other body exudates. Several attempts have been made to produce aerogel-like xerogels under ambient conditions to minimize the shrinkage.…”
Section: Xerogel Functional Materialsmentioning
confidence: 99%
“…Biopolymeric xerogels are porous networks of many unique and desirable properties that have been widely studied for different biomedical applications including controlled and sustained drug delivery, wound dressing and healing applications, tissue engineering scaffolds, and other applications [ 23 ]. Owing to the biocompatibility, non-cytotoxicity, and non-immunogenicity of the biopolymers, biopolymeric xerogels are considered to be a safer option than inorganic and synthetic materials in medical applications [ 1 , 59 ].…”
Section: Biopolymeric Xerogels In Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopolymeric X-G are porous architectures of varying peculiar and enchanting properties that undergone versatile studies for versatile biomedical uses such as manipulatable and sustained drug conveyance, wound dressing as well as repairing uses, tissue engineering scaffolds, and so on [43]. As a result of their biocompatibility, zero-cytotoxicity, and nil-immunogenicity, biopolymeric X-G are perceived to be safer in comparison with inorganic as well as synthetic substrates for medical uses [42][43][44].…”
Section: Biopolymeric X-g In Biomedical Usesmentioning
confidence: 99%
“…reported the platelet-mediated blood coagulation cascade of silk scaffolds (mulberry and non-mulberry) to provide a new direction related to post-implant complications . In a recent study, Cheng et al demonstrated the hemostatic properties of silk fibroin xerogels prepared by free-radical cross-linking (generated by riboflavin) under ultraviolet light . Additionally, several reports also suggested that silk fibroin blended with other polymers ( e.g ., polyethylene glycol (PEG) and alginate) or bioactive molecules (yolk-shell particles and plant derived nanocellulose particles) showed an enhanced hemostatic efficiency. …”
Section: Introductionmentioning
confidence: 99%